Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1074/jbc.m113.482646
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Increases Mitochondrial Energy Formation in L6 Muscle Cell Cultures

Abstract: Background: Metformin is widely believed to inhibit mitochondrial respiration. Results: Metformin increased phosphocreatine recovery from dinitrophenol or azide in intact cells, increased MTT reduction, left ATP levels unchanged, and increased free AMP. Conclusion: Metformin stimulated mitochondrial energy production. Significance: Distinct mechanisms for metformin other than mitochondrial inhibition, such as the inhibition of breakdown of AMP proposed in our work, need to be pursued.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 56 publications
2
24
1
2
Order By: Relevance
“…11 In the present study, peak plasma lactate after supramaximal exercise was measured as an index of glycolysis, as suggested by Vytla and Ochs. 12 There was no significant difference in peak plasma lactate between the placebo and metformin groups (7.8 AE 2.6 vs 7.5 AE 3.0 mmol/L, respectively; P = 0.75; effect size 0.08; Fig. 4).…”
Section: Lactate Peakmentioning
confidence: 82%
“…11 In the present study, peak plasma lactate after supramaximal exercise was measured as an index of glycolysis, as suggested by Vytla and Ochs. 12 There was no significant difference in peak plasma lactate between the placebo and metformin groups (7.8 AE 2.6 vs 7.5 AE 3.0 mmol/L, respectively; P = 0.75; effect size 0.08; Fig. 4).…”
Section: Lactate Peakmentioning
confidence: 82%
“…Likewise, it was shown that in permeabilized vastus lateralis muscle fibers of type 2 diabetes patients treated with metformin (2000±200 mg/day) Complex I-dependent respiratory capacity was not different compared with healthy control subjects, indicating that mitochondrial Complex I respiration is not inhibited by metformin [35]. Surprisingly, in L6 muscle cell cultures [36] and in skeletal muscle of kinase dead AMPK mice [21] metformin even increased mitochondrial energy formation. The discrepancies across the literature could be caused by differences in species, dosing regimens, muscle fiber types, and the methods used to determine the effect of metformin on the mitochondria.…”
Section: Discussionmentioning
confidence: 97%
“…We infer the latter two from the absence of a detectable effect of chronic metformin treatment on myocardial glucose uptake, lactate production, or oxygen consumption during ischaemia. Rather, the ATP-conserving effect of chronic metformin treatment may reflect enhanced mitochondrial efficiency during ischaemia (i.e., increased ATP production per mole of O 2 consumption), as observed with metformin treatment in skeletal muscle under metabolic stress [37]. Alternatively, it is possible that activation of AMPK by metformin decreased ATP utilization for anabolic processes [26].…”
Section: Discussionmentioning
confidence: 99%